Underfill composition

The underfill composition with citraconimide compound and additives addresses the limitations of existing materials by providing a cured product with low dielectric properties and improved penetrability for semiconductor encapsulation.

JP2024179024APending Publication Date: 2024-12-26SHIN ETSU CHEMICAL CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2023097507
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-14
Publication Date
2024-12-26

AI Technical Summary

Technical Problem

Existing underfill materials for semiconductor encapsulation, such as epoxy resins, thermosetting resins, and thermoplastic resins, have high dielectric constants and dielectric loss tangents, making them unsuitable for high-frequency applications, and are hard and brittle, limiting their use in semiconductor encapsulation.

Method used

An underfill composition comprising a citraconimide compound, epoxy resin, epoxy resin curing agent, curing accelerator, and inorganic filler, which provides a cured product with low dielectric constant and loss tangent, improved penetrability, and flexibility.

Benefits of technology

The composition achieves excellent dielectric properties with low dielectric constant and loss tangent, ensuring effective penetration and flexibility, suitable for high-frequency applications in semiconductor encapsulation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024179024000001
    Figure 2024179024000001
  • Figure 2024179024000002
    Figure 2024179024000002
  • Figure 2024179024000003
    Figure 2024179024000003
Patent Text Reader

Abstract

To provide an underfill composition having a low dielectric constant and a low dielectric loss tangent.SOLUTION: The underfill composition contains the following components (A), (B), (C), (D) and (E): (A) a citraconimide compound; (B) an epoxy resin; (C) an epoxy resin curing agent; (D) a curing accelerator; and (E) an inorganic filler. The citraconimide compound (A) is a biscitraconimide compound represented by the following formula (1). (In the formula (1), A represents a divalent organic group.)SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an underfill composition using a citraconic imide compound. [Background technology]

[0002] As electrical equipment becomes smaller, lighter, and more functional, the mainstream mounting method for semiconductor chips is shifting from pin insertion to surface mounting. Among these, the flip chip method is a method in which a semiconductor chip is mounted on the wiring pattern surface of an organic substrate via multiple bumps, and underfill is filled in the gaps between the organic substrate and the semiconductor chip and between the solder bumps (Patent Document 1).

[0003] In recent years, the speed and capacity of signals used in electronic devices such as mobile communication devices, base station equipment, network infrastructure devices such as servers and routers, and large computers are increasing year by year. Accordingly, the printed wiring boards mounted on these electronic devices need to be compatible with high frequencies such as the 20 GHz range, and low dielectric properties such as low relative permittivity and low dielectric loss tangent that enable reduction of transmission loss are required for underfills. In addition to the above-mentioned electronic devices, new systems that handle high-frequency wireless signals are being put into practical use and planned for use in the ITS field (automobiles and transportation systems) and the indoor short-range communication field, and low dielectric properties are also required for underfills used in printed wiring boards mounted on these devices. In addition, a small coefficient of linear expansion (CTE) of underfill is also important in suppressing warpage and improving yield during board manufacturing.

[0004] Epoxy resins widely used in underfills tend to have relatively high dielectric constants and dielectric loss tangents (Patent Document 2). On the other hand, thermosetting resins such as modified polyphenylene ether resins and maleimide resins, and thermoplastic resins such as fluororesins, styrene resins, and liquid crystal polymers are known as materials with low dielectric constants and low dielectric loss tangents (Patent Documents 3 to 7). However, all of these materials have high melt viscosities, and the resulting cured products are hard and brittle, making them suitable for applications such as printed wiring boards, but difficult to use as semiconductor encapsulants such as underfills. It has also been disclosed that a citraconic imide resin composition can provide a cured product with excellent dielectric properties and heat resistance (Patent Documents 8 and 9), but no studies have been conducted on its use as an underfill. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2022-63247 A [Patent Document 2] JP 2022-133311 A [Patent Document 3] Patent Publication No. 2022-77400 [Patent Document 4] JP 2019-99710 A [Patent Document 5] JP 2018-177931 A [Patent Document 6] Patent Publication No. 2022-1628 [Patent Document 7] Patent Publication No. 2022-35328 [Patent Document 8] JP 2023-018240 A [Patent Document 9] JP 2022-147022 A Summary of the Invention [Problem to be solved by the invention]

[0006] Therefore, an object of the present invention is to provide an underfill composition that has excellent penetration properties and that gives a cured product with a low dielectric constant and a low dielectric loss tangent. [Means for solving the problem]

[0007] As a result of intensive research aimed at solving the above problems, the present inventors have found that the following underfill composition containing a citraconic imide compound can achieve the above object, and have completed the present invention. That is, the present invention provides the following underfill composition.

[0008] [1] An underfill composition comprising the following components (A), (B), (C), (D) and (E): (A) Citraconimide Compound (B) Epoxy resin (C) Epoxy resin hardener (D) Curing accelerator (E) Inorganic filler [2] The underfill composition according to [1], wherein the (A) citraconic imide compound is a biscitraconimide compound represented by the following formula (1): [ka] (In formula (1), A is a divalent organic group.) [3] The underfill composition according to [2], wherein A in formula (1) is selected from the group represented by the following structure and a hydrocarbon group derived from a dimer acid skeleton: [ka] (* means a bond with a nitrogen atom in a citraconimide group. n is 1 to 20.) [4] The underfill composition according to any one of [1] to [3], wherein (C) the epoxy resin curing agent is at least one selected from the group consisting of a phenol compound, an acid anhydride compound, and an active ester compound. [5] The underfill composition according to any one of [1] to [4], wherein the (D) curing accelerator comprises one or more selected from the group consisting of imidazole curing accelerators, organophosphorus curing accelerators, and tertiary amine curing accelerators. [6] (B) The underfill composition according to any one of [1] to [5], wherein the epoxy resin has two or more epoxy groups in one molecule. [7] 1 to 100 parts by mass of the (B) component relative to 100 parts by mass of the (A) component, (B) the molar equivalent ratio of the functional group reactive with the epoxy group contained in the curing agent of component (C) is 0.1 to 8.0 relative to 1 molar equivalent of the epoxy group contained in the epoxy resin; The underfill composition according to any one of [1] to [6], wherein the amount of the component (D) is 0.01 to 20 parts by mass per 100 parts by mass of the component (A). [8] (A) The underfill composition according to any one of [1] to [7], wherein the citraconic imide compound has a number average molecular weight of 200 to 10,000. [9] (E) The underfill composition according to any one of [1] to [8], wherein the inorganic filler is spherical silica having an average particle size of 0.01 to 5 μm produced by a sol-gel method.

[10] The underfill composition according to any one of [1] to [9], wherein (E) the inorganic filler is present in an amount of 20 to 80 mass % when all components in the resin composition are taken as 100 mass %. Effect of the Invention

[0009] The underfill composition of the present invention has excellent penetration properties, and the cured product thereof has excellent dielectric properties (low dielectric constant and low dielectric tangent), and therefore the composition of the present invention is useful for underfill applications. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described in detail below.

[0011] (A) Citraconimide Compound The component (A) used in the present invention is a citraconic imide compound. A citraconic imide group is a maleimide group in which one hydrogen atom is replaced with a methyl group. Due to the effect of this methyl group, the compound not only exhibits a lower dielectric constant and a lower dielectric tangent than maleimide compounds of the same skeleton, but also has a lower melting point and improved compatibility with other components.

[0012] The citraconic imide compound of component (A) is not particularly limited with respect to its properties at room temperature or its number average molecular weight, but it preferably has a number average molecular weight of 200 to 10,000, more preferably 200 to 5,000, and even more preferably 200 to 2,000. In this specification, the number average molecular weight is a number average molecular weight calculated using polystyrene standards and measured by gel permeation chromatography (GPC) under the following measurement conditions. [GPC measurement conditions] Developing solvent: Tetrahydrofuran (THF) Flow rate: 0.35mL / min Detector: Refractive index detector (RI) Column: TSK Guardcolumn SuperH-L TSKgel SuperHZ4000(4.6mmI.D.×15cm×1) TSKgel SuperHZ3000(4.6mmI.D.×15cm×1) TSKgel SuperHZ2000 (4.6mmI.D.×15cm×2) (All manufactured by Tosoh Corporation) Column temperature: 40℃ Sample injection volume: 5 μL (0.2% by mass in THF solution)

[0013] From the viewpoints of ease of procurement of the amine compound as the raw material, solubility of the citraconic acid compound in a solvent, and ease of synthesis, the citraconic acid compound of component (A) is preferably a biscitraconimide compound having two citraconic acid groups in one molecule, and is particularly preferably a biscitraconimide compound represented by the following formula (1).

[0014] [ka] (In formula (1), A has a divalent organic group.)

[0015] In order to obtain low elasticity and excellent dielectric properties after curing (low relative dielectric constant and low dielectric tangent), the divalent organic group represented by A in the citraconimide compound is more preferably selected from the group represented by the following structure and a hydrocarbon group derived from a dimer acid skeleton.

[0016] [ka] (* means a bond with a nitrogen atom in a citraconimide group. n is 1 to 20.)

[0017] Among the divalent organic groups represented by A, hydrocarbon groups that do not have an aromatic ring and contain a linear or alicyclic structure, such as groups derived from diamines such as 2-methyl-pentamethylenediamine, 2,2,4-trimethylhexamethylenediamine, and 1,4-cyclohexanedimethaneamine (i.e., groups obtained by removing the two amino groups from the diamines), are particularly preferred from the viewpoint of reducing the viscosity of the underfill composition.

[0018] Dimer acid is a liquid dibasic acid mainly composed of a dicarboxylic acid with 36 carbon atoms, produced by dimerization of unsaturated fatty acids with 18 carbon atoms, which are derived from natural products such as vegetable oils. The dimer acid skeleton is not a single skeleton, but has multiple structures, and there are several types of isomers. Representative dimer acids are classified as linear (a), monocyclic (b), aromatic (c), and polycyclic (d). In this specification, the dimer acid skeleton refers to a group derived from a dimer diamine having a structure in which the carboxy group of such a dimer acid is substituted with a primary aminomethyl group. That is, the hydrocarbon group derived from the dimer acid skeleton possessed by the citraconimide compound of component (A) is preferably a branched divalent hydrocarbon group in which two carboxy groups are substituted with methylene groups in each of the dimer acids shown in (a) to (d) below. Furthermore, when the citraconic imide compound of component (A) has a hydrocarbon group derived from a dimer acid skeleton, the hydrocarbon group derived from the dimer acid skeleton preferably has a structure in which the carbon-carbon double bond in the hydrocarbon group derived from the dimer acid skeleton is reduced by a hydrogenation reaction, from the viewpoint of the heat resistance and reliability of the cured product.

[0019] [ka]

[0020] The citraconic imide compound of the component (A) may be used alone or in combination of two or more kinds. In the underfill composition of the present invention, the proportion of component (A) in the entire composition is preferably 10 to 75 mass %, more preferably 20 to 65 mass %, and even more preferably 30 to 50 mass %.

[0021] (B) Epoxy resin The epoxy resin (B) is added for the purpose of promoting the reaction of the citracone imide compound (A).

[0022] The epoxy resin preferably has two or more epoxy groups in one molecule, and any conventionally known epoxy resin can be used. Examples of the epoxy resin include bisphenol-type epoxy resins such as bisphenol A-type epoxy resins, bisphenol F-type epoxy resins, and bisphenol S-type epoxy resins; novolac-type epoxy resins such as phenol novolac-type epoxy resins, cresol novolac-type epoxy resins, bisphenol A novolac-type epoxy resins, and bisphenol F novolac-type epoxy resins; alicyclic epoxy resins such as dicyclopentadiene-type epoxy resins and 3,4-epoxycyclohexenylmethyl-3',4'-epoxycyclohexenecarboxylate; polyfunctional phenol-type epoxy resins such as resorcinol-type epoxy resins and resorcinol novolac-type epoxy resins; stilbene-type epoxy resins, triazine skeleton-containing epoxy resins, fluorene skeleton-containing epoxy resins, triphenol alkane-type epoxy resins, biphenyl-type epoxy resins, xylylene-type epoxy resins, biphenyl aralkyl-type epoxy resins, naphthalene-type epoxy resins, and diglycidyl ether compounds of polycyclic aromatics such as anthracene, and phosphorus-containing epoxy resins obtained by introducing a phosphorus compound into these. Among these, bisphenol A type epoxy resins, dicyclopentadiene type epoxy resins, biphenylaralkyl type epoxy resins and naphthalene type epoxy resins are preferably used. These may be used alone or in combination of two or more.

[0023] The blending amount of the epoxy resin (B) is preferably 1 to 100 parts by mass, more preferably 2 to 80 parts by mass, and even more preferably 3 to 50 parts by mass, per 100 parts by mass of the component (A). When the blending amount of the epoxy resin (B) is within this range, a cured product having low dielectric properties (low dielectric constant and low dielectric tangent) can be obtained.

[0024] (C) Epoxy resin hardener The epoxy resin curing agent (C) is added for the purpose of reacting with the epoxy group contained in the epoxy resin (B). The epoxy resin curing agent may have a functional group that reacts with the epoxy group, and among them, at least one selected from amine compounds, phenol compounds, acid anhydride compounds, and active ester compounds is preferable. Among them, phenol compounds are more preferable from the viewpoint of the dielectric properties of the composition.

[0025] The amine compound may be a generally known one. From the viewpoint of handling property and moisture resistance reliability, aromatic amine compounds are preferred. For example, aromatic diaminodiphenylmethane compounds such as 3,3'-diethyl-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetramethyl-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetraethyl-4,4'-diaminodiphenylmethane; 2,4-diaminotoluene, 1,4-diaminobenzene, 1,3-diaminobenzene, etc. are preferred, and more preferred are aromatic diaminodiphenylmethane compounds such as 3,3'-diethyl-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetramethyl-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetraethyl-4,4'-diaminodiphenylmethane. These may be used alone or in combination of two or more.

[0026] The amine compound may be liquid or solid at room temperature (20 to 30°C). There is no problem in blending the amine compound as it is, but blending the solid amine compound as it is increases the viscosity of the resin composition, which significantly deteriorates the workability. Therefore, it is preferable to melt-mix the amine compound with the epoxy resin in advance, and it is preferable to melt-mix the amine compound with the epoxy resin in a specific blending ratio described later at a temperature range of 70 to 150°C for 1 to 2 hours. If the mixing temperature is less than 70°C, the amine compound may not be sufficiently compatible, and if the temperature exceeds 150°C, the amine compound may react with the epoxy resin and increase the viscosity. In addition, if the mixing time is less than 1 hour, the amine compound may not be sufficiently compatible, which may lead to an increase in viscosity, and if the mixing time exceeds 2 hours, the amine compound may react with the epoxy resin and increase the viscosity.

[0027] The phenol compound may be a generally known one. For example, phenol novolac resin, naphthalene ring-containing phenol resin, aralkyl type phenol resin, triphenol alkane type phenol resin, biphenyl skeleton-containing aralkyl type phenol resin, biphenyl type phenol resin, alicyclic phenol resin, heterocyclic phenol resin, naphthalene ring-containing phenol resin, resorcinol type phenol resin, allyl group-containing phenol resin such as novolac type allyl phenol resin, bisphenol type phenol resin such as bisphenol A type resin and bisphenol F type resin, etc. may be mentioned. These may be used alone or in combination of two or more.

[0028] The acid anhydride compound can be a generally known one. For example, 4-methylcyclohexane-1,2-dicarboxylic anhydride, 3,4-dimethyl-6-(2-methyl-1-propenyl)-1,2,3,6-tetrahydrophthalic anhydride, 1-isopropyl-4-methyl-bicyclo[2.2.2]oct-5-ene-2,3-dicarboxylic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, hexahydrophthalic anhydride, methylhimic anhydride, pyromellitic dianhydride, maleic alloocimene, benzophenonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetrabisbenzophenonetetracarboxylic dianhydride, (3,4-dicarboxyphenyl)ether dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, etc. can be mentioned. These may be used alone or in combination of two or more.

[0029] The active ester compound can be generally known. For example, the active ester compound includes a dicyclopentadiene type phenolic resin structure, an active ester compound including a phenol novolac structure, an active ester compound including a naphthalene ring structure, an active ester compound including an aralkyl type phenolic resin structure, an active ester compound including a triphenolalkane type phenolic resin structure, an active ester compound including a biphenyl skeleton-containing aralkyl type phenolic resin structure, an active ester compound including a biphenyl type phenolic resin structure, an active ester compound including an alicyclic phenolic resin structure, an active ester compound including a heterocyclic phenolic resin structure, an active ester compound including a naphthalene ring-containing phenolic resin structure, an active ester compound including a resorcinol type phenolic resin structure, an active ester compound including an allyl group-containing phenolic resin structure, an active ester compound including a bisphenol A type resin structure, an active ester compound including a bisphenol type phenolic resin structure such as a bisphenol F type resin, etc. These may be used alone or in combination of two or more.

[0030] The amount of the epoxy resin curing agent is preferably such that the molar equivalent ratio of the functional group in the epoxy resin curing agent to 1 molar equivalent of the epoxy group in the (B) component is 0.1 to 8.0, more preferably 0.5 to 6.0, and particularly preferably 1.0 to 4.0. If the molar equivalent ratio is less than 0.1, unreacted epoxy groups remain, and adhesion may decrease, while if it exceeds 8.0, the moisture absorption rate of the cured product increases, and cracks may occur during reflow or temperature cycles. In the present invention, the equivalent weight is the molecular weight per functional group.

[0031] (D) Curing accelerator The curing accelerator of component (D) may be any that accelerates the curing of the citraconic imide compound (A), and may be any commonly known accelerator, such as an imidazole-based curing accelerator, an organic phosphorus-based curing accelerator, a tertiary amine-based curing accelerator, etc. Among them, it is preferable to use an imidazole-based curing accelerator in order to suppress the viscosity of the composition. Examples of the curing accelerator of component (D) include phosphines such as triphenylphosphine, tributylphosphine, tri(p-methylphenyl)phosphine, and tri(nonylphenyl)phosphine; phosphine-borane complexes such as triphenylphosphine-triphenylborane; and phosphonium borane complexes such as tetraphenylphosphonium tetraphenylborate, tetraphenylphosphonium tetra-p-tolylborate, p-tolyltriphenylphosphonium tetra-p-tolylborate, and tri-tert-butylphosphonium tetraphenylborate. phosphate salts; organic phosphorus compounds such as bis(tetrabutylphosphonium)dihydrogenpyromellitate; tertiary amine compounds such as triethylamine, benzyldimethylamine, α-methylbenzyldimethylamine, and 1,8-diazabicyclo[5.4.0]undecene-7; salts of tertiary amine compounds such as 1,8-diazabicyclo[5.4.0]undecene-7; imidazole compounds such as 2-methylimidazole, 2-phenylimidazole, 2-ethyl-4-methylimidazole, and 2-phenyl-4-methylimidazole. Among these, salts of tertiary amine compounds and organic phosphorus compounds are preferred, and salts of 1,8-diazabicyclo[5.4.0]undecene-7 and tetraphenylphosphonium tetraphenylborate are more preferred. The component (D) may use either a single type alone, or a combination of two or more types.

[0032] The blend amount of the (D) curing accelerator is preferably 0.01 to 20 parts by mass, and more preferably 0.5 to 10 parts by mass, per 100 parts by mass of the (A) component.

[0033] (E) The inorganic filler is added for the purposes of improving the resin strength of the underfill composition and reducing thermal expansion. Examples of inorganic fillers include silicas (such as fused silica, crystalline silica, and cristobalite), alumina, silicon nitride, aluminum nitride, boron nitride, titanium oxide, glass fiber, and magnesium oxide. The particle size of the inorganic filler is preferably adjusted appropriately depending on the gap size of the semiconductor device, that is, the width of the gap between the substrate and the semiconductor chip. The gap size is typically 10 to 200 μm, and in this case, from the viewpoint of the viscosity of the underfill composition and the linear expansion coefficient of the cured product, the inorganic filler is preferably spherical silica having an average particle size (d50: median diameter) of 0.01 to 5 μm, more preferably spherical silica having an average particle size of 0.05 to 2 μm.

[0034] (E) In order to control the average particle size and particle size distribution of the inorganic filler, the sol-gel method or the deflagration method is most suitable. The spherical silica produced by these methods is more spherical than fused silica, and has the advantage that the particle size distribution can be easily designed. The sol-gel method and the deflagration method may be conventionally known methods. Among them, it is more preferable to use silica produced by the sol-gel method from the viewpoint of penetration into thin films.

[0035] It is preferable that 80% by mass or more, particularly 90 to 100% by mass, and especially 95 to 100% by mass of the total inorganic filler (E) is spherical silica produced by a sol-gel method. If it is 80% by mass or more, the flowability of the underfill composition is good.

[0036] The blending amount of the (E) inorganic filler is preferably 20 to 80 mass %, and more preferably 40 to 60 mass %, when the total amount of all components in the composition is 100 mass %. If it is less than 20 mass %, the expansion coefficient of the cured product may be high. If it exceeds 80 mass %, the viscosity of the underfill composition may be high, and the penetration into the gap may be poor.

[0037] In order to strengthen the bond strength between the (A) and (B) components and the inorganic filler, it is preferable to use an inorganic filler that has been surface-treated in advance with a coupling agent such as a silane coupling agent or a titanate coupling agent. Examples of such coupling agents include epoxy silanes such as γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; amino silanes such as N-β(aminoethyl)-γ-aminopropyltrimethoxysilane, reaction product of imidazole and γ-glycidoxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, and N-phenyl-γ-aminopropyltrimethoxysilane; and mercaptosilanes such as γ-mercaptosilane and γ-episulfidoxypropyltrimethoxysilane. The amount of the coupling agent used in the surface treatment and the surface treatment method are not particularly limited.

[0038] Other Additives In addition to the above components (A) to (E), other additives may be added to the underfill composition of the present invention as necessary within the scope of not impairing the object and effect of the present invention. Such additives include flame retardants, ion trapping agents, antioxidants, adhesion promoters, stress reducing agents, colorants, etc.

[0039] The flame retardant is added for the purpose of imparting flame retardancy. There is no particular limitation on the flame retardant, and any known flame retardant can be used, such as a phosphazene compound, a silicone compound, zinc molybdate-supported talc, zinc molybdate-supported zinc oxide, aluminum hydroxide, magnesium hydroxide, or molybdenum oxide.

[0040] The ion trapping agent is added for the purpose of trapping ion impurities contained in the resin composition and preventing thermal deterioration and moisture absorption deterioration. The ion trapping agent is not particularly limited and any known agent can be used, and hydrotalcites, bismuth hydroxide compounds, rare earth oxides, etc. may be used.

[0041] The antioxidant is not particularly limited, and examples thereof include n-octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, n-octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)acetate, neododecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, dodecyl-β-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, ethyl Octadecyl-α-(4-hydroxy-3,5-di-t-butylphenyl)isobutyrate, Octadecyl-α-(4-hydroxy-3,5-di-t-butylphenyl)isobutyrate, Octadecyl-α-(4-hydroxy-3,5-di-t-butyl-4-hydroxyphenyl)propionate, 2-(n-octylthio)ethyl-3,5-di-t-butyl-4-hydroxyphenylacetate, 2-(n-octadecylthio)ethyl-3, 5-di-t-butyl-4-hydroxyphenyl acetate, 2-(n-octadecylthio)ethyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, 2-(2-stearoyloxyethylthio)ethyl-7-(3-methyl-5-t-butyl-4-hydroxyphenyl)heptanoate, 2-hydroxyethyl-7-(3-methyl-5-t-butyl-4-hydroxyphenyl)propionate, pentaethyl Phenolic antioxidants such as rhythritol tetrakis [3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate]; sulfur-based antioxidants such as dilauryl-3,3'-thiodipropionate, dimyristyl-3,3'-thiodipropionate, distearyl-3,3'-thiodipropionate, ditridecyl-3,3'-thiodipropionate, and pentaerythrityl tetrakis (3-laurylthiopropionate);Examples of phosphorus-based antioxidants include tridecyl phosphite, triphenyl phosphite, tris(2,4-di-t-butylphenyl)phosphite, 2-ethylhexyl diphenyl phosphite, diphenyl tridecyl phosphite, 2,2-methylene bis(4,6-di-t-butylphenyl)octyl phosphite, distearyl pentaerythritol diphosphite, bis(2,6-di-t-butyl-4-methylphenyl)pentaerythritol diphosphite, and 2-[[2,4,8,10-tetrakis(1,1-dimethylethyl)dibenzo[d,f][1,3,2]dioxaphosphepin-6-yl]oxy]-N,N-bis[2-[[2,4,8,10-tetrakis(1,1-dimethylethyl)dibenzo[d,f][1,3,2]dioxaphosphepin-6-yl]oxy]-ethyl]ethanamine.

[0042] The adhesion promoter is not particularly limited as long as it is a known adhesion promoter and can achieve the effects of the present invention. In order to impart adhesiveness or tackiness (pressure-sensitive adhesiveness), an adhesion promoter may be included as necessary. Examples of adhesion promoters include urethane resins, phenolic resins, terpene resins, and silane coupling agents. Among these, silane coupling agents are preferred for imparting adhesiveness.

[0043] The silane coupling agent is not particularly limited, and examples thereof include silane coupling agents such as n-propyltrimethoxysilane, n-propyltriethoxysilane, n-octyltrimethoxysilane, n-octyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, 2-[methoxy(polyethyleneoxy)propyl]-trimethoxysilane, methoxytri(ethyleneoxy)propyltrimethoxysilane, 3-glycidyloxypropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-isocyanatopropyltriethoxysilane, and 3-isocyanatopropyltrimethoxysilane.

[0044] The amount of other additives to be added varies depending on the purpose of the composition, but is usually 10% by mass or less of the total composition.

[0045] [Method of producing the composition] The underfill resin composition of the present invention can be produced by the following method. For example, the components (A) to (E) are mixed, stirred, dissolved and / or dispersed, either simultaneously or separately, while being heated as necessary, to obtain a mixture of the components (A) to (E). Preferably, the mixture of the components (A) to (E) may be obtained by adding the epoxy resin curing agent (C) to the mixture of the components (A), (B), (D) and (E), and stirring, dissolving and / or dispersing the mixture. Depending on the intended use, at least one of a flame retardant, a polymerization initiator and an ion trapping agent may be added to and mixed with the mixture of the components (A) to (E). Each component may be used alone or in combination of two or more.

[0046] In the method for producing the composition, the device for mixing, stirring, and dispersing is not particularly limited. Specifically, for example, a mortar and pestle machine equipped with a stirring and heating device, a two-roll mill, a three-roll mill, a ball mill, a planetary mixer, or a mass colloider may be used, and these devices may be used in appropriate combination.

[0047] [Cured Product of Underfill Composition] The curing and molding method and curing and molding conditions of the underfill composition of the present invention may be known, but preferably, a thermal oven cure is first performed at 100-120°C for 0.5 hours or more, and then at 150-175°C for 3 hours or more. Heating at 100-120°C for 0.5 hours or more can suppress the generation of voids after curing. Furthermore, heating at 150-175°C for 3 hours or more can provide sufficient cured product properties. EXAMPLES

[0048] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. In Tables 1 and 2, the blend amounts are indicated by parts by mass.

[0049] The components used in the examples and comparative examples are shown below. In the following, the number average molecular weight (Mn) was measured by gel permeation chromatography (GPC) using polystyrene as the standard under the following measurement conditions. [GPC measurement conditions] Developing solvent: Tetrahydrofuran (THF) Flow rate: 0.35mL / min Detector: Refractive index detector (RI) Column: TSK Guardcolumn SuperH-L TSKgel SuperHZ4000(4.6mmI.D.×15cm×1) TSKgel SuperHZ3000(4.6mmI.D.×15cm×1) TSKgel SuperHZ2000 (4.6mmI.D.×15cm×2) (All manufactured by Tosoh Corporation) Column temperature: 40℃ Sample injection volume: 5 μL (0.2% by mass in THF solution)

[0050] (A) Citraconimide Compound Synthesis Example 1 (Production of Citraconimide Compound, Formula (2)) A 2L glass four-neck flask equipped with a stirrer, a Dean-Stark tube, a cooling condenser and a thermometer was added with 52.29g (0.45 mol) of 2-methylpentamethylenediamine, 111.0g (0.99 mol) of citraconic anhydride and 150g of toluene to prepare a reaction solution, which was then stirred at 80°C for 3 hours to synthesize an amic acid. After that, 40g of methanesulfonic acid was added to the reaction solution, which was then heated to 110°C and stirred for 16 hours while distilling off the by-product water, and the reaction solution was washed five times with 200g of ion-exchanged water. After that, 130.1g (yield 95%) of the target product (formula (2), (A1), number average molecular weight 510) was obtained as a brown liquid at room temperature by vacuum stripping at 60°C. [ka]

[0051] Synthesis Example 2 (Production of Citraconimide Compound, Formula (3)) A 2L glass four-neck flask equipped with a stirrer, a Dean-Stark tube, a cooling condenser and a thermometer was added with 71.2g (0.45 mol) of 2,2,4-trimethylhexamethylenediamine, 111.0g (0.99 mol) of citraconic anhydride and 150g of toluene to prepare a reaction solution, which was then stirred at 80°C for 3 hours to synthesize an amic acid. After that, 40g of methanesulfonic acid was added to the reaction solution, which was then heated to 110°C and stirred for 16 hours while distilling off the by-product water, and the reaction solution was washed five times with 200g of ion-exchanged water. After that, 149.7g (yield 96%) of the target product (formula (3), (A2), number average molecular weight 590) was obtained as a brown liquid at room temperature by vacuum stripping at 60°C. [ka]

[0052] (B) Epoxy resin (B1) Bisphenol A type epoxy resin (jER828EL: manufactured by Mitsubishi Chemical Corporation, liquid at 25°C, epoxy group equivalent 189) (B2) Biphenyl aralkyl type epoxy resin (NC-3000: manufactured by Nippon Kayaku Co., Ltd., softening point 56°C, epoxy group equivalent 273)

[0053] (C) Epoxy resin hardener (C1) Novolac-type allylphenol resin (MEH-8000H: manufactured by Meiwa Kasei Co., Ltd., phenol hydroxyl group equivalent: 141) (C2) 3,3'-diethyl-4,4'-diaminodiphenylmethane (Kayahard AA, manufactured by Nippon Kayaku Co., Ltd., amino group equivalent: 63.5) (C3) 4-Methylcyclohexane-1,2-dicarboxylic anhydride (Rikacid MH: manufactured by New Japan Chemical Co., Ltd., acid anhydride equivalent: 168) (C4) Active ester compound containing a dicyclopentadiene-type phenolic resin structure (HPC-8000-65T: manufactured by DIC Corporation, active ester group equivalent 223, toluene varnish / solid content 65%) Tables 1 and 2 are shown in terms of solid content.

[0054] (D) Curing accelerator (D1) 2-Ethyl-4-methylimidazole (2E4MZ: manufactured by Shikoku Kasei Holdings Co., Ltd.) (D2) 2-Phenyl-4-methylimidazole (2P4MZ: Shikoku Kasei Holdings Co., Ltd.) (D3) Bis(tetrabutylphosphonium) dihydrogen pyromellitate (BTBP-pyromellitic acid: manufactured by Hokko Chemical Industry Co., Ltd.) (D4) Trimellitic acid salt (36%) and phenolic resin salt (46%) of 1,8-diazabicyclo[5.4.0]undecene-7 (DBU) (U-CAT SA838A: San-Apro Co., Ltd.)

[0055] (E) Inorganic filler (E1) Silica filler produced by the sol-gel method (KE-S150: manufactured by Nippon Shokubai Co., Ltd., average particle size 1.5 μm) (E2) Filler produced by the deflagration method (SO-E4-SX: manufactured by Admatechs Co., Ltd., average particle size 1.0 μm) (E3) Fused silica (LVS-516H: manufactured by Tatsumori Co., Ltd., average particle size 0.6 μm)

[0056] (F) Maleimide Compound 1,6-Bismaleimide-(2,2,4-trimethyl)hexane (product name: BMI-TMH, manufactured by Daiwa Chemical Industry Co., Ltd.) The above (F) maleimide compound was used in Comparative Example 4 to demonstrate the superiority of the citraconic imide compound.

[0057] The above components were mixed in the amounts (parts by mass) shown in Tables 1 and 2 to obtain underfill compositions. Each composition and the cured product of each composition were evaluated for penetration, dielectric constant, dielectric tangent, and coefficient of linear expansion (CTE1) by the methods shown below. The results are shown in Tables 1 and 2. The "equivalent ratio" shown in Tables 1 and 2 refers to the ratio of the molar equivalent (active hydrogen equivalent) of the functional group of the epoxy resin curing agent in component (C) to 1 molar equivalent of the epoxy group contained in the epoxy resin in component (B).

[0058] 1. Penetration test A test piece with a 50 μm gap was prepared by sandwiching and fixing two 30 mm × 50 mm glass plates with a 50 μm thick polyimide tape. The test piece was heated to 120° C., and each underfill composition of the examples and comparative examples was poured into the gap, and the time required for the composition to penetrate 30 mm was measured. The time to reach 30 mm was evaluated as "Good" when it took 180 seconds or less, "Fair" when it took more than 180 seconds, and "Poor" when it did not reach 30 mm.

[0059] 2. Dielectric constant and dielectric tangent A frame with a diameter of 200 mm and a thickness of 150 μm was prepared, and each underfill composition of the Examples and Comparative Examples was sandwiched between a 50 μm-thick release-treated PET film (E7006, manufactured by Toyobo) and molded using a vacuum press (manufactured by Nikko Materials) at 180°C for 5 minutes to obtain a cured product. The cured product was removed from the PET film and further cured at 165°C for 3 hours to obtain a cured resin film. Using the cured resin film, a network analyzer (E5063-2D5 manufactured by Keysight Corporation) was connected to a strip line (manufactured by Keycom Corporation) to measure the relative dielectric constant and dielectric loss tangent of the cured resin film at a frequency of 10 GHz.

[0060] 3. Measurement of coefficient of linear expansion (CTE) The above cured products were each processed into test pieces of 5 x 5 x 15 mm, and the test pieces were then set in a thermal dilatometer TMA8140C (manufactured by Rigaku Corporation). The heating program was set to a heating rate of 10°C / min, and a constant load of 19.6 mN was applied, after which the dimensional change of the test pieces was measured between 25°C and 260°C. The linear expansion coefficient was calculated from the dimensional change in the temperature range from 0°C to 40°C, and this was taken as the CTE.

[0061] [Table 1] [Table 2]

[0062] From the results of Tables 1 and 2, it is clear that the underfill composition containing a citraconimide compound, an epoxy resin, an epoxy resin curing agent, a curing accelerator and an inorganic filler has excellent penetration into thin films, and the cured product has excellent dielectric properties (low relative dielectric constant and low dielectric loss tangent). Therefore, the composition of the present invention is useful for underfill applications.

Claims

1. An underfill composition comprising the following components (A), (B), (C), (D) and (E): (A) Citraconimide compound (B) Epoxy resin (C) Epoxy resin curing agent (D) Curing accelerator (E) Inorganic filler

2. 2. The underfill composition according to claim 1, wherein the citraconic imide compound (A) is a biscitraconimide compound represented by the following formula (1): 【Chemistry 1】 (In formula (1), A is a divalent organic group.)

3. 3. The underfill composition according to claim 2, wherein A in formula (1) is selected from the group represented by the following structure and a hydrocarbon group derived from a dimer acid skeleton. 【Chemistry 2】 (* means a bond with a nitrogen atom in a citraconimide group. n is 1 to 20.)

4. 2. The underfill composition according to claim 1, wherein the epoxy resin curing agent (C) is at least one selected from the group consisting of amine compounds, phenol compounds, acid anhydride compounds and active ester compounds.

5. 2. The underfill composition according to claim 1, wherein the curing accelerator (D) comprises at least one member selected from the group consisting of imidazole curing accelerators, organophosphorus curing accelerators, and tertiary amine curing accelerators.

6. 2. The underfill composition according to claim 1, wherein the epoxy resin (B) has two or more epoxy groups in one molecule.

7. 1 to 100 parts by mass of component (B) relative to 100 parts by mass of component (A); (B) the molar equivalent ratio of the functional group reactive with the epoxy group contained in the curing agent of component (C) is 0.1 to 8.0 relative to 1 molar equivalent of the epoxy group contained in the epoxy resin; 2. The underfill composition according to claim 1, wherein the amount of component (D) is 0.01 to 20 parts by mass per 100 parts by mass of component (A).

8. 2. The thermosetting resin composition according to claim 1, wherein the citraconic imide compound (A) has a number average molecular weight of 200 to 10,000.

9. 2. The underfill composition according to claim 1, wherein the inorganic filler (E) is spherical silica having an average particle size of 0.01 to 5 μm produced by a sol-gel process.

10. 2. The underfill composition according to claim 1, wherein the inorganic filler (E) is present in an amount of 20 to 80% by mass when all components in the resin composition are taken as 100% by mass.

Citation Information

Patent Citations

  • Ethercitraconimide compound, preparation thereof and composition containing this compound

    JP1989210408A

  • Epoxy resin composition for semiconductor encapsulation, semiconductor device using the same, and semiconductor manufacturing method

    JP2014521754A

  • Thermosetting citraconimide resin composition

    JP2022147022A

  • Thermosetting resin composition

    JP2023021515A

  • Resin composition and molded article

    JP2018177931A